Naturalization and citizenship: who benefits? : liberalizing access to citizenship has labor market benefits for immigrants and can improve their assimilation - Gathmann, Christina; Monscheuer, Ole (IZA world of labor, 2020)
The perceived lack of economic or social integration by immigrants in their host countries is a key concern in the public debate. Research shows that the option to naturalize has considerable economic and social benefits for eligible immigrants, even in countries with a tradition of restrictive policies. First-generation immigrants who naturalize have higher earnings and more stable jobs. Gains are particularly large for immigrants from poorer countries. Moreover, citizenship encourages additional investment in skills and enables immigrants to postpone marriage and fertility. A key question is: does naturalization promote successful integration or do only those immigrants most willing to integrate actually apply?
Keywords: Graue Literatur